Effects of limonin treatment on the survival of random skin flaps in mice - Zhang, Ting; Huang, Qing; Gan, Kaifeng; Zhou, Ke; Hu, Keqi; Ding, Wei; Jin, Jiale; Li, Jin (Frontiers in Surgery, 2023)
Random skin flap is commonly used in plastic and reconstructive surgery, however, distal part of skin flap often occurs ischemia and necrosis. Limonin, with bioactivities of anti-inflammation, anti-apoptosis and anti-oxidative stress, may be effective for skin flap survival. In our study, random flap model was performed in mice to explore the role of limonin in the survival of skin flap. On postoperative day 7, the necrosis of skin flaps was observed, while visualization of blood flow below the tissue surface was detected through Laser Doppler blood flow imaging (LDBFI). Then flap tissues were acquired to assess and levels of angiogenesis, apoptosis and oxidative stress. The results showed that limonin decreased necrosis and edema of skin flaps compared with the control group, with more blood flow in the flap under LDBFI detection. Limonin treatment also increased the mean vessels density, elevated the expression levels of angiogenic proteins (matrix metallopeptidase 9, vascular endothelial growth factor, Cadherin5) and antioxidant proteins [superoxide dismutase 1 (SOD1), endothelial nitric oxide synthase, heme oxygenase], and reduced the expression of apoptotic factors (BAX, CYC, Caspase3). In summary, limonin could effectively enhance the survival of random skin flap, the potential mechanism may attribute to the induction of angiogenesis, and inhibition of apoptosis and oxidative stress.